Disclosing Product Placements of Fast Food to Children: The Importance of Reinforcing the Use of Disclosures and the Age of Children. Issue 11 (18th September 2020) - Uribe, Rodrigo; Fuentes-García, Alejandra
ABSTRACT: Product or brand placement, the integration of brand/products into TV programs/films, is one of the most controversial forms of promotion. Based on its embedded character, the European Union promulgated in 2010 a norm that obligates broadcasters to disclose the presence of placement. Taking the case of fast food marketing, this paper examines the effects of using disclosures and reinforcing their use during a program (only at the beginning vs. at the beginning and after a commercial break) on children at different ages (9, 12 and 15) in terms of the awareness of the nature of placement, and brand effects (recall and preference). The results showed that (1) reinforcing the use of disclosures increased the awareness of placements; (2) both forms of disclosures (single and reinforced) raised brand recall and limited brand preference of the advertised brand; older children (3) increased the awareness of placements and decreased their brand preference; and also (4) enhanced the effect of disclosures on awareness and brand preference.